Bioenergy and Invasive Plants: Quantifying and Mitigating Future Risks. (June 2014) - Barney, Jacob N.
Abstract: The United States is charging toward the largest expansion of agriculture in 10, 000 years with vast acreages of primarily exotic perennial grasses planted for bioenergy that possess many traits that may confer invasiveness. Cautious integration of these crops into the bioeconomy must be accompanied by development of best management practices and regulation to mitigate the risk of invasion posed by this emerging industry. Here I review the current status of United States policy drivers for bioenergy, the status of federal and state regulation related to invasion mitigation, and survey the scant quantitative literature attempting to quantify the invasive potential of bioenergy crops. A wealth of weed risk assessments are available on exotic bioenergy crops, and generally show a high risk of invasion, but should only be a first-step in quantifying the risk of invasion. The most information exists for sterile giant miscanthus, with preliminary empirical studies and demographic models suggesting a relatively low risk of invasion. However, most important bioenergy crops are poorly studied in the context of invasion risk, which is not simply confined to the production field; but also occurs in crop selection, harvest and transport, and feedstock storage. Thus, I propose a nested-feedback risk assessment (NFRA) that considers the entire bioenergy supply chain and includes the broad components of weed risk assessment, species distribution models, and quantitative empirical studies. New information from the NFRA is continuously fed back into other components to further refine the risk assessment; for example, empirical dispersal kernels are utilized in landscape-level species distribution models, which inform habitat invasibility studies. Importantly, the NFRA results in a relative invasion risk to known species (e.g., is giant reed a higher or lower invasion risk than johnsongrass). This information is used to design robust mitigation plans that include record keeping, regular scouting and reporting, prudent harvest and transport practices that consider species biology, and eradication protocols as an ultimate precaution. Finally, a socio-political balance must be struck (i.e., a cost-benefit analysis) among our energy choices that consider the broader implications, which includes the risk of future invasions.